Ecofriendly Extract of Euphorbia hirta as Corrosion Inhibitor on Mild Steel in Sulphuric Acid Medium - KASTHURI*, P.K.; ARULANANTHAM†, A. (Asian Journal of Chemistry, 2024)
The influence of the addition of acid extract of Euphorbia hirta on the corrosion of mild steel in 1 M H2SO4 was studied by weight loss measurement. The inhibition efficiency increases with extract concentration and immersion period. The effect of temperature studied indicated that inhibition efficiency increased with temperature. The negative value of the free energy of adsorption indicates spontaneous adsorption. The inhibitor obeys Temkin adsorption isotherm. The inhibition activity is due to the adsorption of active components which are found in the Euphorbia hirta extract.